Implementasi Metode SMART Untuk Penentuan Platform Pembelajaran Jarak Jauh Masa Pandemi - Rajiansyah, Rajiansyah; Fajri, Ahmad (STMIK Budi Darma, 2021)
The pandemic period is difficult times for all nations and countries around the world because the pandemic period is a period that limits many activities carried out as usual due to an outbreak of the Covid-19 virus as the most contagious and quite deadly virus, including in learning activities for an educational institution for the sake of education. break the rope of the spread of a larger virus so that a platform is used that helps in carrying out the teaching and learning process, the many types of platforms currently available make it difficult to determine the most appropriate platform for its use based on several criteria such as usability, affordability, maintability, accessibility and compatibility. the selection using a decision support system to facilitate the decision-making process appropriately, the process of using a decision support system using the SMART (Simple Multi Attribute Rating Technique) method, the results obtained are ah A2 with a value of 0.92